2020
DOI: 10.1038/s41598-020-58334-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of molecular and pharmacological modulators of mitochondrial fatty acid oxidation

Abstract: fatty acid oxidation (fAo) is a key bioenergetic pathway often dysregulated in diseases. the current knowledge on fAo regulators in mammalian cells is limited and sometimes controversial. previous FAO analyses involve nonphysiological culture conditions or lack adequate quantification. We herein described a convenient and quantitative assay to monitor dynamic fAo activities of mammalian cells in physiologically relevant settings. the method enabled us to assess various molecular and pharmacological modulators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 78 publications
0
37
0
Order By: Relevance
“…22,39 Yet recently it has also been demonstrated that in the cell lines MCF-7 and T47D, PerHx did not directly impair FAO. 40 Even more, the same mechanism was described for Etomoxir (another CPT-1 inhibitor), which impaired IL-4 mediated polarization independently of CPT-1 inhibition by an offtarget inhibition of the Adenine Nucleotide Translocator (ANT) and depletion of cytoplasmic CoA. 41 Further studies are needed to unravel the effect of PerHx on mitochondrial respiration and immune cells, considering that PerHx dosage may have to be adjusted per patient to prevent side effects.…”
Section: Discussionmentioning
confidence: 91%
“…22,39 Yet recently it has also been demonstrated that in the cell lines MCF-7 and T47D, PerHx did not directly impair FAO. 40 Even more, the same mechanism was described for Etomoxir (another CPT-1 inhibitor), which impaired IL-4 mediated polarization independently of CPT-1 inhibition by an offtarget inhibition of the Adenine Nucleotide Translocator (ANT) and depletion of cytoplasmic CoA. 41 Further studies are needed to unravel the effect of PerHx on mitochondrial respiration and immune cells, considering that PerHx dosage may have to be adjusted per patient to prevent side effects.…”
Section: Discussionmentioning
confidence: 91%
“…It is noted that the effects of Rano on the cell may not be limited to FAO inhibition. Although, noted as a partial FAO inhibitor, Rano was found to lack the FAO-interfering activity in complete media with or without serum ( 35 ), despite showing FAO-inhibiting ability in our FAO assay utilizing glucose-deprivation and a single FAO source (18C unsaturated fatty acid oleate).…”
Section: Discussionmentioning
confidence: 94%
“…Accordingly, the impairment in FAO observed in astrocytes derived from induced pluripotent stem cells isolated from Alzheimer's disease patients is corrected by PPARβ/δ agonists (Konttinen et al, 2019). The specificity of the metabolic modifiers ranolazine (Ranexa) and trimetazidine, initially described as partial FAO inhibitors that target the HAD (or 3-KAT) activity of the trifunctional protein HADHA, has been recently questioned (Ma et al, 2020).…”
Section: Fa Oxidation (Fao) In Astrocytes: the "Missing Link"mentioning
confidence: 99%